(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Correspondence of the size of the foot with the dimensions of the internal shape of the shoe is one of the most important indicators of the shoe quality. It is known that the lasts dimensions in length and girth differ than the foot dimensions. The article presents the results of studies of the feet sizes of men in Uzbekistan in the amount of 994 people, which were carried out in order to determine the conformity of the size of the feet with the size of shoe lasts. Foot sizes were divided into three age groups. For each size group, the statistical parameters of size features were determined, as well as the relationship between the length of the foot and the girth. Based on the data obtained, the relationship between the average length and girth of the foot with the size of the shoe lasts of medium width for three age groups of men was determined